Expression Of The Concept Of Mother And Child In English And Uzbek Proverbs (Progress Annals: Journal of Progressive Research, 2025)
Proverbs serve as an essential cultural and linguistic tool that reflects the values, beliefs, and traditions of a society. This study examines the representation of the mother-child relationship in English and Uzbek proverbs, following a comparative analysis approach. By categorizing proverbs into three main themes—(1) the role of mothers, (2) childrearing, and (3) the emotional bond between mother and child—this research highlights both the universal and culturally specific aspects of maternal influence. Findings indicate that both English and Uzbek cultures emphasize the unconditional love, sacrifice, and wisdom of mothers. However, Uzbek proverbs place a stronger focus on religious and moral duties, while English proverbs highlight emotional support and individualism. The study also incorporates insights from scholars such as Wolfgang Mieder, David Cheal, and Uzbek linguists to provide a broader context. Understanding these proverbs enriches cross-cultural appreciation and deepens our comprehension of family dynamics in different societies